Variations in TAS1R taste receptor gene family modify food intake and gastric cancer risk in a Korean population. Issue 11 (16th August 2016) - Choi, Jeong‐Hwa; Lee, Jeonghee; Choi, Il Ju; Kim, Young‐Woo; Ryu, Keun Won; Kim, Jeongseon
Abstract : T1R taste receptor mediates umami and sweet taste perception and regulates physiological metabolism. This study examines whether polymorphisms in TAS1R are associated with the food intake and the susceptibility to gastric cancer (GC). We found that TAS1R polymorphisms are associated with dietary consumption, which may be linked to GC risk. TAS1R1 rs34160967 may also modify the male‐specific risk for GC independent of diet in Koreans. Abstract : Scope: Human taste receptor type 1 ( TAS1R, T1R ) gene family mediates the perception of umami and sweet tastes and regulates metabolism. This study investigated whether variants in the TAS1R are associated with food intake and susceptibility to gastric cancer (GC). Methods and results: A total of 1131 Koreans including 377 GC cases were analyzed to determine the dietary intake and genotype for 25 variants in TAS1R genes. Among the genotyped polymorphisms, six loci with a minor allele frequency >0.05 were tested for an association with dietary intake and GC risk. Findings suggest that TAS1R polymorphisms were associated with a variety of food intake that is beyond the known T1R‐taste association. Furthermore, differential consumption for cigarettes and citrus fruits by TAS1R genetic variants may be linked to GC risk in males and females, respectively. Additionally, in males, TAS1R1 rs34160967 heterozygote showed an increased risk of GC (odds ratio: 1.52, 95% confidence interval: 1.10–2.09), independent of dietary intake. However, this GC‐risk effect of TAS1R variants was not evident in females. Conclusions: Genetic variants in TAS1R were associated with dietary consumption, which may be associated with GC risk. TAS1R1 rs34160967 may also modify the risk for GC independent of diet in Korean males.